Working with AI: Can stress bring happiness? - Loureiro, S. M. C. (2023)
This paper explores the effect of artificial intelligence (AI) on employee happiness and proposes a model founded on stress and coping theory to analyze the effect of benign stress on employee happiness and its indirect effect via employee engagement. It combines semi-structured interviews with employees working alongside AI algorithms and agents and surveys 200 employees to assess the proposed model. The results demonstrate that incorporating AI in the workplace can generate stress and affect human well-being but can also be a motivational factor instead of a concern, and that employee engagement plays an essential role in mediating the relationship.